Strategies to Organise Professionally to Advise, Prepare and Assure Sustainability-Oriented Management Reports - Ingaramo, Eduardo (Ediciones UNL. Secretaría de Extensión de la UNL, 2020)
The objective of this research work is to answer the question “How can we organise to provide professional services to advise, prepare and assure sustainability-oriented management reports?” and it is aimed at professionals in Economics both in the present and for the future.There is no simple or direct answer to this question. It is about changing deeply-rooted structures in most companies which do not see the advantages of sustainable management in our country yet. This proposal is presented as an essay based on theoretical arguments  from different socioeconomic, environmental, political and humanist schools of thought. It considers factors which include the personal and professional sustainability of millennials and centennials, the market of professional services such as consultancy and audit, their existing organisational forms and the development of a business plan for the organisation of professional services.The purpose of this work is to be useful for the training of sustainabilityoriented professionals in the field of Economics.